Sistem Penentuan Indeks Massa Tubuh Menggunakan Pengolahan Citra Digital - Safitri, Evyra Rizki (Jurnal Ilmu Komputer; Vol 17 No 1 (2024): Jurnal Ilmu KomputerDO - 10.24843/JIK.2024.v17.i01.p07, 2024)
Obesity stands as a significant and perilous health concern, holding utmost importance for the well-being of the body. To mitigate the associated health risks, its identification can be achieved through the utilization of a standardized technique known as the Body Mass Index (BMI) for calculating the optimal body weight. To get information about person’s BMI value and category, data on weight and height are needed, which are then calculated to produce the appropriate BMI value and category. To implement a more pragmatic strategy, this study will be executed by developing an application that captures images of the human body using a mobile phone camera. Image processing with digital image processing stages such as preprocessing, morphology, BS and then calculating the weight and height and BMI category. Based on the system test that was carried out, the best approximate value was obtained at a distance 200cm with a body height value is 96% while the body weight is 90,8% and accuracy value of BMI category is 80%.